HUBUNGAN KOMUNIKASI DALAM KELUARGA DENGAN PERKEMBANGAN PSIKOLOGIS ANAK ASIA SEKOLAH (6-12 TAHUN) DI DESA TUMARATAS DUA KECAMATAN LANGOWAN BARA - Kapantow, Jein Olifia; Tuda, Josef; Ponidjan, Tati (Universitas Sam Ratulangi)
Abstract: Good communication in families is very important in times of psychological development of school-aged children. The purpose of research to determine the relationship of communication in families with school-age children development. Cross sectional method, with the total sampling of as many as 40 of the respondents. The Data processed with SPSS for analysis by the method of chi-square test at 95% significance level (Î±= 0.05). The research results showed that respondents with a good category for communication within the family as well as the development of appropriate psychological there are a total of 16 respondents (84.2%) and respondents are categorized well for communication within the family but not in accordance with the development of the psychological as much as 3 of the respondents (15.8%). the respondents by category is bad for communication within the family but in accordance with the psychological development of school-aged children as much as 9 respondents (42,9%) and respondents who considered bad for communication within the family but did not match psychological development of as many as 12 respondents (57,1%). Conclusion there is a meaningful relationship communication in families with the psychological development of school-aged children (6-12 years) in the village of Tumaratas west of two district LangowanÂ with value p = 0.007 and value analysis of the Odds Ratio (OR) obtained the value of 7,111. Keywords: Communication family, Child psychologically Abstrak: Komunikasi yang baik dalam keluarga sangatlah penting dalam masa perkembangan psikologis anak usia sekolah. Tujuan penelitian untuk mengetahui hubungan komunikasi dalam keluargaÂ dengan perkembangan anak usia sekolah. Metode cross sectional, dengan total sampling sebanyak 40 responden. Data diolah dengan program SPSS untuk di analisa dengan metode uji chi-square pada tingkat kemaknaan 95% (Î±=0,05). Hasil penelitian menunjukan bahwa responden dengan kategori baik untuk komunikasi dalam keluarga serta perkembangan psikologis anak yang sesuai ada sebanyak 16 responden (84,2%) dan responden yang dikategorikan baik untuk komunikasi dalam keluarga tetapi tidak sesuai dengan perkembangan psikologis anak sebanyak 3 responden(15,8%). responden dengan kategori buruk untuk komunikasi dalam keluarga tetapi sesuai dengan perkembangan psikologis anak usia sekolah sebanyak 9 responden (42,9%) dan responden yang dikategorikan buruk untuk komunikasi dalam keluarga tetapi perkembangan psikologis anak tidak sesuai sebanyak 12 responden (57,1%). KesimpulanÂ ada hubungan yang bermakna komunikasi dalam keluarga dengan perkembangan psikologis anak usia sekolah (6-12 tahun) di desa Tumaratas Dua Kecamatan Langowan Barat dengan nilai p = 0,007 dan nilai analisis Odds Ratio (OR) diperoleh nilai 7,111. Kata kunci : Komunikasi keluarga, Psikologis Anak